The Role of Law Enforcement Officials: The Dilemma Between Professionalism and Political Interests - Karimullah, Suud Sarim (Jurnal Hukum dan Peradilan, 2024)
This study delves deeply into the complex dilemma between professionalism and political interests that often grip performance and shape public perceptions of law enforcement officials. With a phenomenological approach applied through integrative and connective literature analysis, this study combines various perspectives, combining findings from multiple relevant studies to create a more holistic and comprehensive understanding. The conclusions of this study firmly state that strengthening the professionalism of law enforcement officers is a significant endeavor because professionalism in law enforcement is an essential foundation for upholding justice, transparency, and human rights. Achieving a high level of professionalism requires a holistic and integrated approach, including institutional reform, adequate supervision, continuing education, and developing a robust organizational culture. Success in law enforcement depends on the strict application of rules and building positive relationships between law enforcement officers and the communities they serve. Through community-based approaches, respect for human rights, and a commitment to integrity and accountability, law enforcement systems can be strengthened to ensure fair, transparent, and trustworthy justice.